Evolusi Pemasaran Jasa dan Pemasaran Relasional Jasa Pendidikan - Ahmad, Dimas Zuhri; Muin, Abdul (LEMBAGA PENELITIAN & PENGABDIAN MASYARAKAT UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
Marketing management is the activity of analyzing, planning, implementing, and supervising, in order to obtain a favorable level of exchange to achieve organizational goals. The evolution of relational marketing has become very important because education is a service that requires long-term relationships with customers. Relational marketing can help schools to maintain good relationships with customers, increase customer satisfaction, and acquire new customers through recommendations from existing customers. The presentation of this article uses a descriptive approach based on the writings of education experts, trying to find the evolution of marketing and marketing educational services. The conclusion of writing this article is that Educational services marketing is a way to do something where students, parents, school employees, and the community consider schools as community support institutions dedicated to serving the needs of educational service customers while Relational marketing is focused on recruiting and retaining or maintaining educational service customers, the relationship between schools and educational service customers.